“Rukhsah” solat among hospitalized patients: Where are we now? - Jailani R.F.; Ariffin A.C.; Ngadiron H.; Dewa M.N.; Bain M.A.; Shariff M.S.M.; Eyzawiah N.; Rani M.D.M.; Arief Hamid (American Scientific Publishers, 2024)
Indexed by SCOPUS